Carrier Redistribution Between Two Kinds of Localized States in the InGaN/GaN Quantum Wells Studied by Photoluminescence - Xing, Yao (Nanoscale Res Lett, 2019)
The InGaN/GaN multi-quantum wells (MQWs) are prepared at the same condition by metal-organic chemical vapor deposition (MOCVD) except the thickness of cap layers additionally grown on each InGaN well layer. The photoluminescence (PL) intensity of the thin cap layer sample is much stronger than that of thicker cap layer sample. Interestingly, the thick cap layer sample has two photoluminescence peaks under high excitation power, and the PL peak energy-temperature curves show an anomalous transition from reversed V-shaped to regular S-shaped with increasing excitation power. Meanwhile, it exhibits a poorer thermal stability of thick cap layer sample under higher excitation power than that under lower excitation power. Such an untypical phenomenon is attributed to carrier redistribution between the two kinds of localized states which is induced by the inhomogeneous distribution of indium composition in thick cap layer sample. Furthermore, the luminescence of deep localized states has a better thermal stability, and the luminescence of shallow localized states has a poor thermal stability. In fact, such a severer inhomogeneous indium distribution may be caused by the degradation of subsequent epitaxial growth of InGaN/GaN MQWs region due to longer low-temperature GaN cap layer growth time.